Performance Evaluation and Optimization of the Maize Shelling Operation of the Multi-Purpose Farm Vehicle - Nsubuga, Denis; Kabenge, Isa; Zziwa, Ahamada; Kiggundu, Nicholas; Wanyama, Joshua; Banadda, Noble (CIGR Journal, 2020)
Small-scale farmers register high postharvest losses partly due to failure to carry out primary processing operations. Most of the maize shellers on the Ugandan market lead to high percentage of broken maize grains thus raising the risk of aflatoxin infection during storage. In this study, the operation of an existing maize sheller on the market with a shelling speed of 870 rpm for maize at 13 % moisture content was tested. The main objective of this study therefore was twofold; (i) to develop and evaluate a maize sheller and (ii) to optimize the multi-purpose vehicle shelling operation. The improved maize sheller was designed, fabricated, evaluated and optimized using a factorial experiment with shelling speed and moisture content as the main effects at three levels. Analysis of Variance was done using R-studio. A cost-benefit analysis of the shelling technology was conducted. The obtained results showed that a reduction in moisture content and an increase in shelling speed increased the shelling efficiency, the grain damage percentage, output capacity and the cleaning efficiency. The optimum moisture content and the shelling speed of the multi-purpose vehicle maize shelling were 13% and 896 rpm respectively. Except the shelling efficiency, the results of the modified maize sheller were significantly different (p<0.05) from those of the market sheller. The payback period was 1.37 years while the benefit-cost ratio was 1.07. The optimized maize shelling operation of the multi-purpose vehicle is therefore economically viable.
Keywords: Maize Shelling, multipurpose vehicle, Physical properties, engineering properties